Pengarauh Memorable Tourism Experience dan Perceived Risk Terhadap Revisit Intention Pada Destinasi Wisata Curug Cigentis di Kabupaten Karawang - Hanna Rachmawati Febriyani; Abdul Yusuf (Jurnal Ilmiah Wahana Pendidikan, 2022)
The spread of the Covid-19 virus in various countries has had an impact on the tourism industry, including in Indonesia. West Java was one of the areas visited by many local and foreign tourists before the pandemic. Karawang Regency is a city in West Java that has various tourist destinations that have the potential to be developed. The biggest potential for natural tourism in Karawang Regency comes from waterfalls. One of the waterfalls is Curug Cigentis. The high number of COVID-19 cases in Karawang, raises the perception of risk that makes tourists also consider visiting tourist attractions. In fact, one of the steps to increase revenue in the tourism sector is to create memorable experiences. So that it affects the interest in visiting Curug Cigentis again. This study aims to find out, explain and analyze and test the Effect of Memorable Tourism Experience and Perceived Risk on Revisit Intention at Curug Cigentis Tourism Destinations in Karawang Regency. This research was conducted using quantitative methods with descriptive and verification approaches, namely by collecting presentations, through the analysis process and hypothesis testing as well as making conclusions and suggestions from the research results. The sample in this study was collected using the Issac and Michael formula with an error rate of 10% using a non-probability sampling technique with a purposive sampling approach, obtained 268 samples from 33.220 populations. The analytical techniques used are scale range analysis and path analysis with the help of Method Successive Interval (MSI), Microsoft Excel 2019 program, and SPSS version 25 application. The results of this study indicate descriptively that the variables of memorable tourism experience, perceived risk, revisit intention are in the good category. Based on the results of the verification analysis, the variables of memorable tourism experience and perceived risk influence each other and show the level of influence of the relationship is very strong. The partial effect obtained from the memorable tourism experience and perceived risk variables on revisit intention of each variable is 41,5% and 34,9% with a total simultaneous effect of 76.4% while the rest is influenced by other variables not examined by 23,6%